Midoriya Cake Shop / Muhammad Amirul Hakimi Ramli ... [et al.] - Ramli, Muhammad Amirul Hakimi; Ariffin, Mohd Khairil Hadri; Ismail, Muhd Asyraf; Mustafa, Muhammad Akmal; Ahmad, Muhammad Fadhil (2021)
The Business Model Canvas is used in this study to expose us as an entrepreneurial tool for building a basic business plan and to offer transferable knowledge and skills such as handson experience with the tool, oral communication, critical analysis, and teamwork. There is a nine-block that contains customer segments, value proposition, channels, customer relationship, revenue streams, key resources, key activities, key partner, and cost structure. Each of the nine blocks of the business model canvas must be determined by the company. With the recognition and solution of opportunities, the customer's problem may be solved. Many solutions have been developed to improve the product that is now available on the market to meet the demands of customers. The company must complete all of the blocks in the business model canvas in order to run the business and create the measuring set with scale. The firm has a variety of distribution possibilities for the measurement set with scales, including online stores, merchants, and websites. This product also targeting customers such as kids, adults, and obviously one that very likes cake. Therefore, this business will serve many customers and also bring happiness to others.